ATRAÇÃO E REFRAÇÃO NA EDUCAÇÃO A DISTÂNCIA: CONSTATAÇÕES SOBRE O ISOLACIONISMO E A EVASÃO DO ALUNO - Gisela Biacchi Emanuelli (Revista Gestão Universitária na América Latina, 2011)
The brasilian law of diretrizes e bases da educação encourages long-distance education as an economic and an including resource of access to education and learning. The method has its advantages, but is not enough to prevent the self-taught avoidance. Sample collected in an University of Distrito Federal, comes to confirm the paradox between the attraction, that it has for its economy and flexibility, and refraction of students by virtue of isolation and the need for the teacher. To demonstrate the balance between attraction and refraction of the long- distance learning this work started with that research to general conclusions, endorsed by other researches. The result coincides with the concern of Ministério da Educação of Brazil, which is being long-distance education a tool for education with significant dropout rates.